Problem-Based Learning in Phytochemistry Courses: Its’ Effectiveness in Improving Medical Students’ Critical Thinking Ability Viewed from Cognitive Style - Menap Menap; Faizul Bayani; Saiful Prayogi (Postgraduate, University of Mataram, 2021)
The implementation of the Problem-Based Learning (PBL) model for medical students has long been initiated to be integrated into the learning system and curriculum, however, empirical support for the application of the PBL model to medical students is still weak, becoming an obstacle. On the one hand, the need for critical thinking development among medical students is increasingly urgent, this is related to their future assignments in a more complex health care system that requires critical thinking ability. Our current study aims to evaluate the effectiveness of the problem-based learning (PBL) model on improving the critical thinking ability of medical students in terms of cognitive style. This study is an experimental study (one group pretest-posttest design) involving 21 medical students (medical students') in phytochemistry courses at one of the universities providing medical and nursing science programs in Indonesia. The study started by giving a cognitive style test using the GEFT (Group Embedded Figure Test) instrument to classify students into FD and FI cognitive styles, pretest, learning implementation using the PBL model (carried out for five meetings), and posttest. The pretest and posttest used a critical thinking ability test instrument in the form of an essay test. Descriptive and statistical analyzes were performed to evaluate the effectiveness of the PBL model. The results of the study show that the PBL model has been convincingly effective in improving students' critical thinking ability in phytochemistry courses for both FD/FI cognitive style modes. Based on these findings, we recommend the use of the PBL model in extensive and intensive learning to develop the critical thinking ability of medical students